The use of comics for the improvement of oral and written expression in a second language. - Zarza-Quirós, Aida (My University, 2022)
This work aims to improve fluency in both oral expressions and writing in children. For this purpose, comics will be used as the main didactic resource to put into practice the contents seen after each unit and check their understanding. One of the main objectives to be worked on in Primary Education is written expression, what children write needs to have coherence and cohesion. In addition, oral expression is the importance of being able to communicate with others to transmit any message correctly. For this reason, this didactic proposal of intervention determines a series of activities based on the comic after acquiring the contents and in this way being able to put them into practice using contents and simulating real situations in the environment of the students, being also a motivating, fun and attractive tool for the little ones.
Keywords: comic; writing; visual language; expression skills; didactic resources; Grado en Maestro en Educación Primaria